Colistin Resistance and Management of Drug Resistant Infections. (10th December 2022) - Sharma, Juhi; Sharma, Divakar; Singh, Amit; Sunita, Kumari
Abstract : Colistin resistance is a globalized sensible issue because it has been considered a drug of the last-line resort to treat drug-resistant bacterial infections. The product of the mobilized colistin resistance ( mcr ) gene and its variants are the significant causes of colistin resistance, which is emerging due to the frequent colistin use in veterinary, and these genes circulate among the bacterial community. Apart from mcr genes, some other intrinsic genes and proteins are also involved in colistin resistance. Researchers focus on the most advanced genomics (whole genome sequencing), proteomics, and bioinformatics approaches to explore the question of colistin resistance. To combat colistin resistance, researchers developed various strategies such as the development of newer drugs, the repurposing of existing drugs, combinatorial treatment by colistin with other drugs, a nano-based approach, photodynamic therapy, a CRISPRi-based strategy, and a phage-based strategy. In this timeline review, we have discussed the development of colistin resistance and its management in developing countries.